Fe, Co bimetal activated N-doped graphitic carbon layers as noble metal-free electrocatalysts for high-performance oxygen reduction reaction - Han, C.; Bo, X.; Liu, Jian; Li, M.; Zhou, M.; Guo, L. (Elsevier B.V., 2017)
© 2017 In this work, a novel catalyst in form of Fe, Co bimetallic alloy activated N-doped graphitic carbon layers (NC/Fe10-xCox) without metal core is rationally fabricated through a simple pyrolysis method and applied for efficient oxygen reduction reaction (ORR) catalysis. The NC/Fe10-xCoxcatalysts have exhibited superior electrocatalytic ORR performance comparable to commercial Pt/C via a four-electron pathway under the same loading in alkaline media with outstanding durability and complete methanol tolerance. The improvement of ORR performance can be attributed to the synergistic effect of Fe, Co bimetallic activation on nitrogen-doped graphitic carbon layers, rich pore structure and uniformly dispersed dopants in the carbon matrix.